Worker Stress and Performance Pay: German Survey Evidence - Mehrzad B. Baktash; John S. Heywood; Uwe Jirjahn (Global Labor Organization (GLO), 2021)
While performance pay can benefit firms and workers by increasing productivity and wages, it has also been associated with a deterioration of worker health. The transmission mechanisms for this deterioration remain in doubt. We examine the hypothesis that increased stress is one transmission mechanism. Using unique survey data from the German Socio-Economic Panel, we find performance pay consistently and importantly associates with greater stress even controlling for a long list of economic, social and personality characteristics. It also holds in instrumental variable estimations accounting for the potential endogeneity of performance pay. Moreover, we show that risk tolerance moderates the relationship between performance pay and stress. The risk tolerant receiving performance pay suffer less stress than the risk averse.
Keywords: J33; I31; J32; 330; Performance Pay; Worker Health; Stress; Risk Tolerance